Pengaruh Sikap Berwirausaha, Kreativitas Berusaha Dan Lingkungan Keluarga Terhadap Motivasi Berwirausaha - Fatkhan Zaki Arrafid (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to analyze the influence of motivation, entrepreneurial attitudes and family environment on interest in entrepreneurship. The type of research used is a quantitative method with descriptive analysis. The data collection technique was carried out online with a questionnaire using a Likert scale of one to five and was obtained using a simple random sampling method on 111 respondents with criteria above the age of 18 years. The data analysis techniques used in this research are: Outer Model with calculations of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha and Inner Model with calculations of T statistics, R-Square, f-Square, and VIF using SmartPLS (Partial Least) tools. Square) version 4.0.9.3. The research results show that: 1) Entrepreneurial attitudes have a significant influence on consumer satisfaction. 2) Entrepreneurial creativity has a significant influence on consumer satisfaction. 3) The family environment has a significant influence on consumer satisfaction.